2011
DOI: 10.1007/s10936-011-9193-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Orthography on Speech Production in Chinese

Abstract: The potential role of orthographic representations on spoken word production was investigated with speakers of Chinese, a non-alphabetic and orthographically non-transparent language. Using the response generation procedure, we obtained the well-known facilitation from word-initial phonological overlap, but this effect was unaffected by whether or not responses shared the initial character. In a study which manipulated the visual similarity of the word-initial character, a significant inhibitory effect of orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
(56 reference statements)
0
7
1
Order By: Relevance
“…With English speakers, Damian and Bowers (2003) reported orthographic effects: Priming arising from shared word-initial segments (Bcoffee^, Bcamel^, Bclimate^) was disrupted if one item was substituted with one which had a conflicting wordinitial grapheme (Bcoffee,^Bcamel,^Bkennel^). However, this positive result contrasts with several null findings across various languages (Dutch: Roelofs, 2006;French: Alario, Perre, Castel, & Ziegler, 2007;Mandarin: Bi, Wei, Janssen, & Han, 2009b;Zhang & Damian, 2012), suggesting that if orthographic effects are genuine, the implicit priming task does not reliably detect them. 1 By contrast, a number of recent contributions have demonstrated orthographic effects in spoken word production in tasks which required the learning of novel words.…”
contrasting
confidence: 74%
“…With English speakers, Damian and Bowers (2003) reported orthographic effects: Priming arising from shared word-initial segments (Bcoffee^, Bcamel^, Bclimate^) was disrupted if one item was substituted with one which had a conflicting wordinitial grapheme (Bcoffee,^Bcamel,^Bkennel^). However, this positive result contrasts with several null findings across various languages (Dutch: Roelofs, 2006;French: Alario, Perre, Castel, & Ziegler, 2007;Mandarin: Bi, Wei, Janssen, & Han, 2009b;Zhang & Damian, 2012), suggesting that if orthographic effects are genuine, the implicit priming task does not reliably detect them. 1 By contrast, a number of recent contributions have demonstrated orthographic effects in spoken word production in tasks which required the learning of novel words.…”
contrasting
confidence: 74%
“…Current studies of the lesioned brain and physiological functional study models support the notion that Chinese language processed distinctively when compared to alphabetic languages such as English {7, 28, 29, 4750}. It is demonstrated that orthography in Chinese is more important in accessing semantics rather than phonology {47, 49} and phonology processing in Chinese is distinctive when compared to alphabetic languages {48}. While most studies describing Chinese deep dyslexia employed a model with a developmental approach, Shu and colleagues as well as Yin and colleagues {7, 50} described cases with deep dyslexia that were either trauma- or vascular-related brain lesions, which were explained well by the triangle model.…”
Section: Discussionmentioning
confidence: 85%
“…The literature on written versions of the implicit priming task is still limited, but to our knowledge no inhibitory effects have been reported so far (e.g., Chen & Cherng, 2013, reported a mix of null and positive effects). Zhang and Damian (2012) reported a spoken implicit priming experiment with Mandarin speakers in which visual orthographic similarity among spoken response words resulted in a weak (11 ms) inhibitory effect; however, subsequent control experiments led the authors to attribute this effect to the memorisation stage of the response generation task, rather than reflecting processes genuine to speaking. In short, it is at present unclear whether the inhibitory effect of logographeme overlap which manifests itself in a subset of participants is genuine, and if so, how it could be explained.…”
Section: Discussionmentioning
confidence: 99%